The Asian region and COVID-19: approaches and gaps in controlling the virus. Issue 2 (9th November 2020) - Mehta, Poonam
Abstract : Purpose: The world is facing an unprecedented transformation in its social, economic and financial environments due to the emergence of a new pandemic called coronavirus disease 2019 (COVID-19). The norms on social distancing, lockdowns and sealing of international boundaries are the common measures taken by almost all regions of the world. However, the Asian region is found to have a relatively lesser number of infected cases and deaths due to COVID-19 in comparison to the other regions of the world. The present study has been aimed to review the roles of various factors as approaches, such as technology, business–government collaborations, financial bailouts and policies from government side and geographical and demographical factors of the countries in slowing down the transmission of virus in the Asian region including East Asia, South Asia and South East Asia for controlling COVID-19. Besides, the present study has also emphasised the gaps which have disabled the Asian region in controlling the transmission of virus. Design/methodology/approach: For framing the paper, various articles, national and international reports and academic papers have been reviewed, which are published in the period 2000–2020. The studies are shortlisted on the basis of keywords, such as COVID-19, coronavirus, severe acute respiratory syndrome-like coronavirus ( SARS-CoV-2), pandemic, virus, quarantine, Asia, etc. Findings: The study has emphasised the roles of government, technology, business–government collaborations and geographical and demographical factors of countries as relevant factors in controlling COVID-19. Also, the study has highlighted inefficient health infrastructure, fear of social stigma and misinformation amongst citizens as those gaps where Asian regions are simultaneously found to be unprepared and inefficient to control the pandemic. Research limitations/implications: The present review would aid researchers in explaining the relevance of macro-level factors such as technology, business–government collaborations, government policies and financial bailouts and geographical and demographical factors of the region in controlling the transmission of pandemics and epidemics. Practical implications: The study would assist decision makers, governments and individuals in framing of the various strategies and interventions to control pandemics and epidemics. Social implications: The present study has explained the relevance of various behavioural and social factors as gaps which are responsible for speeding up the transmission of COVID-19. Here, the study would guide the society in taking various right steps during the phase of pandemic and lockdowns. Originality/value: Previously, rarely any study has been found which has reviewed the roles of macro-level factors as approaches and gaps in the context of the Asian region to slow down the transmission of COVID-19.